Pengaruh Model RME Berbasis Etnomatematika Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Matematika Kelas V SDN Gugus 05 Kota Bengkulu - Mirnawati Mirnawati; Victoria Karjiyati; Dalifa Dalifa (Universitas Bengkulu, 2020)
This study aims to determine the effect of the realistic mathematics education (RME) learning model based on etnhnomatematics on the ability of studens to think critically in mathematics learning in class V SDN cluster 05 Bengkulu City. This research is quantitative research. The research was a quasy experiment whit a matching only pretest-posttest control group design study design. The population in this study was SDN Cluster 05 Bengkulu city. The sampling technique used cluster random sampling. The sample inthis study was VA class at SDN 09as an experimental class and VA class SDN 02 as a control class. The instrument used in this study was a description tests sheet. Taking the test twice before and after giving treatment to sample class. Of this research by using SPSS 16.00 for windows. Based analysis of rsearch data is the result of difference beetwen the pretest-posttest control and eksperimen. this difference is evidenced by the significance value od the t test 0,001 < 0,05 means. Result it can be concluded that there are difference in the use of RME bases etnomathematics on mathematics critical thinking.